Prevalence of iatrogenic hypothyroidism in hyperthyroid cats treated with radioiodine using an individualised scoring system. Issue 12 (December 2019) - Fernandez, Yordan; Puig, Jordi; Powell, Roger; Seth, Mayank
Objectives: The aim of this study was to report the prevalence of iatrogenic hypothyroidism, with or without azotaemia, based on the measurement of serum total thyroxine (T4), thyroid-stimulating hormone (TSH) and creatinine concentrations, in hyperthyroid cats undergoing radioiodine ( 131 I) treatment where the 131 I dose was calculated using a previously described scoring system. A secondary aim of the study was to determine the positive and negative predictive values of serum T4 and TSH concentrations obtained 19 days after treatment in order to predict the development of iatrogenic hypothyroidism 6–9 months after 131 I treatment. Methods: Serum T4, TSH and creatinine concentrations were measured 19 days and 6–9 months after 131 I treatment. The prevalence of iatrogenic hypothyroidism was assessed with the results obtained 6–9 months after 131 I treatment. Results: The prevalence of overt and subclinical hypothyroidism 6–9 months after 131 I treatment was 40.0% (22/55 cats) and 12.7% (7/55 cats). Overt hypothyroidism with azotaemia was diagnosed in 8/55 (14.5%) cats. The positive and negative predictive values for the prediction of the development of iatrogenic hypothyroidism 6–9 months after 131 I treatment were 72.2% and 80.0%, respectively, for a low serum T4 concentration, and 75.0% and 44.6%, respectively, for an increased serum TSH concentration. Conclusions and relevance: The use of an individualised scoring system is effective in determining the 131 I dose for the treatment of hyperthyroid cats. However, the prevalence of overt hypothyroidism was higher in comparison with other studies using different dosing protocols. Further studies comparing the efficacy of individualised scoring systems and different fixed doses to determine which method is superior are warranted.